The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fonc.2020.553628
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulation of L Antigen Family Member 3 Associates With Aggressive Progression of Breast Cancer

Abstract: The role of L Antigen Family Member 3 (LAGE3) in breast cancer (BC) has not been sufficiently studied. In this study, we explored the clinical value and biological functions of LAGE3 in BC. Comprehensive analysis of LAGE3 was carried out on The Cancer Genome Atlas, Molecular Taxonomy of Breast Cancer International Consortium and Gene Expression Omnibus datasets. Results showed that LAGE3 expression was higher in BC tissues than in normal breast tissues of public datasets and our local cohort. Moreover, its exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 61 publications
1
11
0
Order By: Relevance
“…Since LAGE3 positively promotes the proliferation of HCC cells and breast cancer cells [ 9 , 11 ], our study involved CCK8 assay, BrdU assay, and cell cycle assay to explore the LAGE3 knockdown effects on the proliferation of HCC cells, and it was observed that the cell proliferation rate of the LAGE3-siRNA group was extraordinarily reduced in SMCC-7721 and Huh-7 cell lines when compared with the control group (Fig. 3 A, B).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Since LAGE3 positively promotes the proliferation of HCC cells and breast cancer cells [ 9 , 11 ], our study involved CCK8 assay, BrdU assay, and cell cycle assay to explore the LAGE3 knockdown effects on the proliferation of HCC cells, and it was observed that the cell proliferation rate of the LAGE3-siRNA group was extraordinarily reduced in SMCC-7721 and Huh-7 cell lines when compared with the control group (Fig. 3 A, B).…”
Section: Resultsmentioning
confidence: 99%
“…Since LAGE3 positively promotes the migration and invasion of HCC cells and breast cancer cells [ 9 , 11 ], migration and invasion of cancer cells are the key driving force for cancer metastasis and the main cause of cancer-related deaths [ 15 , 16 ]. Therefore, scratch healing assay and Transwell assay were adopted to explore the effect of LAGE3 knockdown on the migration and invasion of HCC cells.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations